Good Finance : Integration of Ethics and Shariah in Islamic Finance - Furqani, Hafas; Laldin, Mohamad; Mulyany, Ratna (IJIBE (International Journal of Islamic Business Ethics), 2016)
Islamic Financial industry is moving towards the global integration. There is a considerable acceptance of Islamic financial practices across the globe. Islamic finance is viewed positively as an attractive financial system that could be adopted in modern context. One of the reasons for this acceptance could be due to its ethicalÂ  promises. Islamic finance is perceived as an ethical based finance that is operating with a set of good ethics in financial dealings. With that ethical back up as the underlying principles in financial activities, there is wide expectation that it could offer a different perspective and approach in finance and a coherent perspective for understanding real economic problems faced by human being and hence could elegantly solve the crisis as regularly faced in the conventional financial system. Islamic finance is developed with the aim of capturing the moral high ground of banking and financial practices in an increasingly volatile world by offering a financial philosophy based on the triumph of ethics and dealing with customers in a more humanistic approach for the betterment of society. In this regard, the moral mastery is not only expected to be the hallmark of Islamic financial professionalism, but it is also desired to be naturally integrated in the system and its practitioners. Islamic finance aims to achieve a fair wealth circulation in society, fair and transparent financial dealings and justice in micro and macro dimension. The paper attempts to discuss the concept of ethics in Islamic finance, its basis, principles and objectives in the contemporary world.